Stress Exposure and Psychological Well-being: Study on Beginning Teacher - Mohamad Arief Rafsanjani; Etika Dhewi Rahmawati (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2019)
A beginning teacher is someone who has just started his/her career as a teacher or someone who has just graduated from college and is working as a teacher. This transition from student to worker (as a teacher) is a critical period since it is often associated with stress (Dicke et al., 2015; Smith and Ingersoll 2004). This study examines the relationship between stress exposure (seen from stress exposure in class and outside class) and the psychological well-being of beginning teachers (seen from work enthusiasm and emotional exhaustion). This study is conducted on 325 beginning teachers of senior high schools in Malang as samples collected using a random sampling technique. The data are analyzed by using a Structural Equation Modeling (SEM). The results show that stress exposure in class and outside class has negative effect on work enthusiasm but, on the other hand, had positive effect on emotional exhaustion. This shows that stress exposure has significant effects on beginning teachers’ psychological well-being.